PENGARUH FINANCIAL DISTRESS, LEVERAGE DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI: Studi Empiris pada Perusahaan Manufaktur Sektor Industri Barang dan Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Pratama, Aditya; Setyadi, Edi Joko; Pramono, Hadi; Hartikasari, Annisa Ilma (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The purpose of this study is to analyze and test empirically whether the variables of financial distress, leverage, and profitability can affect accounting conservatism in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The data analysis technique used is panel data regression analysis and uses E-Views 12 software. The sample selection was carried out by purposive sampling, with several restrictions. Based on the panel data regression analysis test, it is known that financial distress and leverage have a significant positive effect on accounting conservatism. Meanwhile, accounting conservatism is significantly negatively affected by profitability. This study has limitations because there are problems with the results of normality, autocorrelation, and heteroscedasticity tests which previously used 184 data samples reduced to 84 data samples and limitations on the observation period.